2019
DOI: 10.1149/2.0191903jss
|View full text |Cite
|
Sign up to set email alerts
|

Impact of UV Nanosecond Laser Annealing on Composition and Strain of Undoped Si0.8Ge0.2 Epitaxial Layers

Abstract: Ultraviolet Nanosecond Laser Annealing (UV-NLA) was performed on 30 nm-thick Si 0.8 Ge 0.2 epitaxial layers. The various regimes encountered, depending on the melt depth after single pulse UV-NLA, are described and discussed in this paper. Energy densities around 2.00 J/cm 2 and above led to the formation of pseudomorphic layers with a strong Ge redistribution. Starting from uniform Si 0.8 Ge 0.2 layers, Ge segregation toward the surface resulted in the formation of a Ge-rich surface layer with up to 55 at.% G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 27 publications
6
18
0
Order By: Relevance
“…For Si0.8Ge0.2 samples, (yellow circles in Figure 13a), it was found that, in the surface melt regime (at 1.55 and 1.59 J/cm²), laser annealing did not cause any relaxation, although the surface had locally started to melt (with a surface coverage lower than 20%, however). For higher energy densities, at the end of the surface melt regime (1.70 and 1.80 J/cm²), solidification started from a non-planar l/s interface [28], leading to the same results as those described in the previous section, i.e. the formation of defects in the whole regrown layer, accompanied by partial relaxation (~30% in this case).…”
Section: Iii2b Impact Of Ge Concentration And/or Thicknesssupporting
confidence: 78%
See 3 more Smart Citations
“…For Si0.8Ge0.2 samples, (yellow circles in Figure 13a), it was found that, in the surface melt regime (at 1.55 and 1.59 J/cm²), laser annealing did not cause any relaxation, although the surface had locally started to melt (with a surface coverage lower than 20%, however). For higher energy densities, at the end of the surface melt regime (1.70 and 1.80 J/cm²), solidification started from a non-planar l/s interface [28], leading to the same results as those described in the previous section, i.e. the formation of defects in the whole regrown layer, accompanied by partial relaxation (~30% in this case).…”
Section: Iii2b Impact Of Ge Concentration And/or Thicknesssupporting
confidence: 78%
“…"30 nm" and "Si0.7Ge0.3"). The Ge depth profiles are not shown here, as their shapes are very similar to the ones shown in Figure 2 (those associated with the 30nm thick Si0.8Ge0.2 and Si0.6Ge0.4 samples were reported in previous papers [28,39]. For energy densities corresponding to the early stages of the surface melt regime (i.e.…”
Section: Iii1c Germanium Impact On Regime Determinationsupporting
confidence: 65%
See 2 more Smart Citations
“…Another alternative is the application of non-conventional thermal sources, like lasers, to post-process semiconductor alloy thin films grown on substrates with high thermal conductivities. 24,25 Such methods allow for achieving extremely high temperature gradients (10 9 K m -1 ) and cooling rates (10 5 K s -1 ), which are required to ensure the stability of the solid/liquid interface. Recently, by using laser processing of amorphous SiGe thin films deposited on silicon substrates, the fabrication of non-dendritic SiGe microstripes was demonstrated with steady-state compositional profiles that can be tuned by applying different constant scan speeds in the range of 0.1-100 mm s -1 .…”
Section: Introductionmentioning
confidence: 99%